Detection of Trichinella spp. in free-ranging carnivores and wild boars in Switzerland. ... - Basso, Walter; Moré, Gastón; Gliga, Diana; Marti, Iris; Müller, Norbert; Lundström-Stadelmann, Britta; Frey, Caroline F. (University of Bern, 2025)
Wolves (Canis lupus lupus) and lynx (Lynx lynx) are officially monitored species in Switzerland. Deceased individuals are subjected to post-mortem examination and collection of baseline health data. The procedure includes an assessment of different infectious agents, including Trichinella spp., the cause of a notifiable zoonotic infection. Between May 2009 and May 2023, a total of 100 wolves and 250 lynx were tested at the National Reference Laboratory for Trichinellosis by the artificial digestion method. Additionally, muscle samples from 8838 wild boars (Sus scrofa), 27 red foxes (Vulpes vulpes), and 23 European badgers (Meles meles), mainly submitted by Swiss hunters, were also analysed for Trichinella infection. Trichinella spp. larvae were detected in 16/100 (16 %) wolves, 41/250 (16.4 %) lynx, 2/27 (7.4 %) red foxes, 0/23 (0 %) badgers, and 1/8838 (0.01 %) wild boars. All positive samples were further tested by multiplex PCR to identify the parasite at the species/genotype level. Two species were ...